Study on the nutritional composition of the sea vegetable Ulva compressa in a brine-based cultivation system - Fricke, Anna; Harbart, Vanessa; Schreiner, Monika; Baldermann, Susanne (Frontiers in Marine Science, 2023)
Driven by the global need of alternative food sources, there is a rising interest in edible macroalgae (seaweeds). In order to provide fresh and healthy seafood even in inland areas, land-based, environmentally controlled seaweed farming is on the rise. Facing several issues, especially the need of suitable cultivation media increases with growing distance from the coast. In order to provide regional solutions and make the cultivation approaches more sustainable, the present study investigates the potential use of natural saline ground water (brine) for the production of the macroalga Ulva compressa in inland cultivation systems. Over a period of 88 days, macroalgal thalli were cultivated in aerated experimental units (120 L) filled with brine-based media or commercial artificial sea water. Physicochemical properties of the cultivation media and the nutritional profile of macroalgal thalli were analyzed after 52 and 88 days of cultivation. The results underline not only the feasibility to use brine in the farming of sea vegetables (e.g. overcoming the lack of seawater and reduction of freshwater use), but also clearly indicate a nutrional value for the U. compressa cultivation, resulting in algal thalli, rich in polyunsaturated fatty acids and carotenoids (e.g. lutein, β carotene). The present findings might serve as a step stone for the further development of brine-based inner land aquaculture systems.